La arquitectura terapéutica desde el enfoque juvenil CAET centro de atención especializada y terapéutica para jóvenes (2022)
Heritage in Colombia is characterized by having a historical process guided towards abandonment, especially tangible or intangible real estate, this, meaning that the main focus within the current problems is only determined from the evolutionary approach, but also born from knowing the history and building resilience from this. In Colombia, heritage is at high risk due to the abandonment that determines urbanization and the cultural deterioration that it generates from the segregation of communities and one of the main ones is that of those who commit crimes. Bogotá, being the main city that houses these two characteristics, generates a main theme on which to focus the project, understanding from research that the main localities with the greatest criminal impact on minors between 15 and 19 years of age are Los Martíes and Santa Fe, like this causing a deterioration in the national historic center, which leaves in danger the culture, architecture and urban impacts that could be generated there.